Vacuum-free processed bulk heterojunction solar cells with E-GaIn cathode as an alternative to Al electrode - Ongul, Fatih; Yuksel, Sureyya Aydin; Bozar, Sinem; Cakmak, Gulbeden; Guney, Hasan Yuksel; Egbe, Daniel Ayuk Mbi; Gunes, Serap (IOP Publishing Ltd, 2015)
In this paper, the photovoltaic characteristics of bulk heterojunction solar cells employing an eutectic gallium-indium (EGaIn) alloy as a top metal contact which was coated by a simple and inexpensive brush-painting was investigated. The overall solar cell fabrication procedure was vacuum-free. As references, regular organic bulk heterojunction solar cells employing thermally evaporated Aluminum as a top metal contact were also fabricated. Inserting the ZnO layer between the active layer and the cathode electrodes (Al and EGaIn) improved the photovoltaic performance of the herein investigated devices. The power conversion efficiencies with and without EGaIn top electrodes were rather comparable. Hence, we have shown that the EGaIn, which is liquid at room temperature, can be used as a cathode. It allows an easy and rapid device fabrication that can be implemented through a vacuum free process.
Keywords: EGaIn; Al; ZnO; vacuum free; POLYMER PHOTOVOLTAIC CELLS; GALLIUM-INDIUM EGAIN; HIGH-PERFORMANCE; LIQUID-METAL; MORPHOLOGY; EFFICIENCY; LAYER; FILMS; Physics